Economic Assessment of Sanitation Interventions in Indonesia - World Bank (Washington, DC, 2014)
Statistics from the UN Joint Monitoring Program show sanitation progress in Indonesia to be off-track coverage has to increase by more than 13 percentage points nationally from 2008 to 2015 to meet the sanitation target of the Millennium Development Goals, which the Government of Indonesia committed to in 2002. However, after being a largely forgotten issue in the 15 years following the Asian financial crisis of 1997-98, sanitation is now receiving increasing attention from all levels of government in Indonesia. Recently the Government of Indonesia has made considerable efforts to mobilize additional resources in order to finance the country's needs for infrastructure projects. The purpose of the Economics of Sanitation Initiative (ESI) is to promote evidence-based decision making using improved methodologies and data sets, thus increasing the effectiveness and sustainability of public and private sanitation spending. Better decision making techniques and economic evidence themselves are also expected to stimulate additional spending on sanitation to meet and surpass national coverage targets. The specific purpose of the ESI phase two studies is to generate robust evidence on the costs and benefits of sanitation improvements in different programmatic and geographic contexts in Indonesia, leading to information about which are more efficient and sustainable sanitation interventions and programs. Basic hygiene aspects are also included, insofar as they affect health outcomes.